White noise path integral approach on the partition function of a semi-flexible biopolymer in a bend and twist worm-like chain model - Monterola, Emmanuel D.; Gemao, Beverly V.; Cubero, Ryan John A. (2011)
Understanding the elastic behavior of polymers is helpful in understanding biological processes like gene regulation and transcription in cells. Thus, in recent years, statistical mechanics of biopolymers has emerged as a field of rapid theoretical and experimental investigation. This interest has been motivated from experiments which probe the function of elasticity of these biopolymers. In this paper, we investigate the partition function of a semi-flexible biopolymer theoretically modeled in a worm-like chain (WLC) model which considers its bend and twist degrees of freedom, We note that this partition function can be expressed as